Cambodia's Cross-Cutting Reforms : Public Financial Management, Decentralization, and Public Administration Reforms - Achievements, Coordination, Challenges, and Next Steps - World Bank Group (World Bank, Phnom Penh, 2019)
This note analyzes the progress of three public sector reforms (Public Financial Management, Public Administration, and Decentralization and Deconcentration) in Cambodia and describes how their design, implementation, and institutional arrangements can be better sequenced and coordinated. It focuses on the overall public sector reform agenda rather than drill into the specifics of individual reforms. Options are identified to strengthen coordination of the civil service, improve general policy sequencing, and manage challenges within the three reform areas. Recommendations to deepen individual reforms are also provided, in particular, to strengthen cross-cutting public administration improvements.